PENGARUH MODEL PEMBELAJARAN DEMONSTRASI BERBANTUAN VIDEO TUTORIAL TERHADAP KETERAMPILAN LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS IV SD NEGERI LAMPER LOR SEMARANG - Kasirin; Afandi, Muhamad; Solikhun, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of students' long jump skills and the lack of student activeness in learning. The demonstration learning model assisted by video tutorials emphasizes the practice of student demonstration skills assisted by video tutorials. This demonstration model assisted by video tutorials is very important because it increases the effectiveness of independent learning through easy-to-understand step-by-step visualization, improves memory, and provides flexible access anytime and anywhere. This media motivates students, facilitates the understanding of abstract concepts, and is efficient for teachers for practical materials. This study aims to determine the effectiveness of the demonstration learning model assisted by video tutorials in improving the squat style long jump skills of fourth-grade students of Lamper Lor Elementary School, South Semarang. Sampling used a purposive sampling technique, with a sample of 26 students in the experimental class and 25 students in the control class. Data collection with a practical test of long jump skills covers 4 aspects. Data analysis includes normality test, homogeneity test and hypothesis test which are processed with the help of SPSS version 26. The results of the study showed that there was a difference in the effectiveness of the demonstration learning model assisted by video tutorials with the conventional learning model in improving the squat style long jump skills of fourth grade students of Lamper Lor Elementary School, South Semarang, which was indicated by the difference in the average posttest score of the experimental group of 86.30 and the control group with an average of 76.50 with a difference of 9.8. The Sig. value (2-tailed) was 0.046 <0.05 which indicated that there was a significant difference between the experimental group and the control group.